Inhibition of human immunodeficiency virus type 1 by niclosamide through mTORC1 inhibition - Niyomdecha, Nattamon (Heliyon, 2020)
Niclosamide has been known to inhibit a number of pH-dependent viruses via the neutralization of endosomal acidic pH. It has also been shown to disrupt the mTORC1 signaling pathway. The replication of many viruses requires mTORC1 activation. Here, we investigated the inhibitory activity of niclosamide against HIV-1, and determined whether mTORC1 inhibition was involved. The cytotoxicity and anti-HIV-1 activity of niclosamide were tested in TZM-bl and SupT1 cells. Niclosamide showed a dose- and time-dependent inhibitory activity against HIV-1 replication, but the inhibition did not involve the reverse transcription and transcription steps. The mechanism of mTORC1 inhibition was explored by using MHY1485, an mTORC1 activator, to reverse the mTORC1 inhibition, which could partially restore HIV-1 replication. In addition, niclosamide was found to downregulate mTORC1 via AMPK activation, resulting in a decreased phosphorylation of the downstream substrates of S6K and 4EBP1. Niclosamide could also reduce the synthesis of HIV-1 p24 protein. Likewise, MHY-1485 could partially reverse the inhibitory effect of niclosamide by increasing the phosphorylation in the mTORC1 pathway and HIV-1 viral protein synthesis. Our findings, therefore, demonstrated the antiviral mechanism of niclosamide is via the AMPK-mTORC1 pathway, which could be a common therapeutic target for various viruses.